Radiochemical Characterization of Algae Products Commercialized for Human Consumption. Issue 3 (September 2016) - Desideri, Donatella; Cantaluppi, Chiara; Ceccotto, Federica; Meli, Maria Assunta; Roselli, Carla; Feduzi, Laura
Abstract : Abstract: Natural radionuclides and 137 Cs were determined by alpha ( 238 U, 234 U, 230 Th, 210 Po, 232 Th, and 228 Th) and gamma spectrometry ( 137 Cs, 40 K, 226 Ra, 210 Pb, and 228 Ra via 228 Ac) in 14 dried seaweeds commercialized for human nutrition in Italy. The study was carried out in order to provide information on the concentrations of natural and artificial radionuclides. Cesium-137 ( 137 Cs) concentrations in all analyzed samples were always <2.0 Bq kg −1 (dry weight), while the naturally occurring radionuclide concentrations were detectable in all the samples and significantly different in the analyzed seaweeds. Potassium-40 ( 40 K) showed a mean activity of 894 Bq kg −1 with a range of 14.1–3, 256 Bq kg −1 . The mean of activity for 210 Po was 5.1 Bq kg −1 with a range of 1.5–13.6 Bq kg −1 . The mean of activity for 210 Pb was 8.9 Bq kg −1 with a range of 2.9–25.7 Bq kg −1 . The mean of 238 U and 226 Ra activity concentration was 4.7 and 8.4 Bq kg −1 with a range of 0.1–27.7 and 3.2–24.6 Bq kg −1, respectively. The mean activity concentrations for 232 Th, 228 Th, and 228 Ra were 0.69, 3.0, and 6.6 Bq kg −1 with ranges of 0.05–3.39, 0.24–15.7, and 0.5–35.6 Bq kg −1, respectively. Radionuclide activity concentrations were within ranges reported in the scientific literature. The committed effective dose due to all the radionuclides analyzed, from ingestion of 1 kg y −1 of seaweeds, accounts for 0.66% of the natural radiation exposure in Italy.